Community dialogue meetings among district leaders improved their willingness to receive COVID-19 vaccines in Western Uganda, May 2021 - Edirisa Juniour Nsubuga; Arthur G. Fitzmaurice; Allan Komakech; Tom Dias Odoi; Daniel Kadobera; Lilian Bulage; Benon Kwesiga; Peter James Elyanu; Alex Riolexus Ario; Julie R. Harris (BMC, 2023)
Abstract Background Widespread COVID-19 vaccine uptake can facilitate epidemic control. A February 2021 study in Uganda suggested that public vaccine uptake would follow uptake among leaders. In May 2021, Baylor Uganda led community dialogue meetings with district leaders from Western Uganda to promote vaccine uptake. We assessed the effect of these meetings on the leaders' COVID-19 risk perception, vaccine concerns, perception of vaccine benefits and access, and willingness to receive COVID-19 vaccine. Methods All departmental district leaders in the 17 districts in Western Uganda, were invited to the meetings, which lasted approximately four hours. Printed reference materials about COVID-19 and COVID-19 vaccines were provided to attendees at the start of the meetings. The same topics were discussed in all meetings. Before and after the meetings, leaders completed self-administered questionnaires with questions on a five-point Likert Scale about risk perception, vaccine concerns, perceived vaccine benefits, vaccine access, and willingness to receive the vaccine. We analyzed the findings using Wilcoxon's signed-rank test. Results Among 268 attendees, 164 (61%) completed the pre- and post-meeting questionnaires, 56 (21%) declined to complete the questionnaires due to time constraints and 48 (18%) were already vaccinated. Among the 164, the median COVID-19 risk perception scores changed from 3 (neutral) pre-meeting to 5 (strong agreement with being at high risk) post-meeting (p < 0.001). Vaccine concern scores reduced, with medians changing from 4 (worried about vaccine side effects) pre-meeting to 2 (not worried) post-meeting (p < 0.001). Median scores regarding perceived COVID-19 vaccine benefits changed from 3 (neutral) pre-meeting to 5 (very beneficial) post-meeting (p < 0.001). The median scores for perceived vaccine access increased from 3 (neutral) pre-meeting to 5 (very accessible) post-meeting (p < 0.001). The median scores for willingness to receive the vaccine changed from 3 (neutral) pre-meeting to 5 (strong willingness) post-meeting (p < 0.001). Conclusion COVID-19 dialogue meetings led to district leaders' increased risk perception, reduced concerns, and improvement in perceived vaccine benefits, vaccine access, and willingness to receive the COVID-19 vaccine. These could potentially influence public vaccine uptake if leaders are vaccinated publicly as a result. Broader use of such meetings with leaders could increase vaccine uptake among themselves and the community.